Letters of old age = (Rerum senilium libri). - Petrarca, Francesco, 1304-1374 (Italica, 2005)
In Letters on Old Age, Aldo Bernardo and his collaborators extend the translation project begun with the Letters on Familiar Matters to the letter collection of Petrarch's old age, the Seniles. In these 128 letters, most of which appear for the first time here in English translation, we find Petrarch's mature judgment on the central issues of early Italian humanism. With Boccaccio, to whom he addresses more letters than anyone else, Petrarch shares his ideas about the literary culture of the age.